Factors of investment decision making in the Malaysian public listed companies: perspectives from individual shareholders and key stakeholders / Arifha Mohamad - Mohamad, Arifha (2020)
Individual shareholders make investment decisions based on their main objectives from the trading activities in reducing risk with high return. This study seeks to identify the level of risk-taking among individual shareholders; the influential factors of the investment that affect the individual shareholders’ investment decision making specifically in the Malaysian Public Listed Companies (PLCs); the main significant factor; the moderating result from the relationship; and the challenges to ensure wise investment decision made by individual shareholders. Using a mixed methodology, questionnaires were distributed to 680 individual shareholders during the company’s Annual General Meeting (AGM) and six key stakeholders were interviewed. Based on the findings, that there was a high level of risk-taking among the individual shareholders in PLCs. The significant factors that influence individual shareholders to invest were accounting information, personal financial needs, advocate recommendations and images of the company. Meanwhile, the individual shareholders in Malaysia did not rely on corporate social responsibility (CSR) in their investment decision. Based on the interviews conducted, the emerging factors discovered were size of company, type of company and technology. This study revealed that among the factors, the most influential factor for decision making was personal financial needs. Since size of company acted as the moderating effect, the result depicted significant relationship only between CSR and investment decision making. Furthermore, the key stakeholders’ perspectives outlined that the challenges faced by the individual shareholders were lack of information, investment culture, lack of investment knowledge and voting power. The limitation of this study lies on its respondents where individual shareholders were used as the unit of analysis while leaving out other investors. Due to a number of constraints, this study only managed to collect a sample from three top sectors listed on Bursa Malaysia, which were trading services sector, industrial product sector and consumer product sector traded by individual shareholders as a representation for a group of individual shareholders’ trading shares in the Malaysian PLCs. This study provides new insight into the development of financial and non-financial factors to the investment decision making in the Malaysian PLCs. Thus, it is recommended that future study can analyze the implications of other factors that may influence investment decision making other than individual shareholders.